Organization Commitment and Five Factor Model of Personality: Theory Recapitulation - Syed, Nida; Saeed, Arfa; Farrukh, Muhammad (Journal of Asian Business Strategy, 2015)
Organizational commitment is one of the most popular psychological construct which plays a vital role in predicting work behavior. There are many approaches to study organizational commitment, and one of them is an individual difference approach. Since organizational commitment is one kind of job attitudes, and personality traits might predispose individual to experience raised or lowered levels of his or her organizational commitment. In connection to the previous studies, this research is aimed to examine the association among big five personality traits (FFM with dimensions of the organizational commitment. A questionnaire was adopted from the previous studies and a total number of 150 responses were gathered from the lecturer/supervisors working in public universities located in Lahore, Pakistan. The results of the research demonstrated that there is a significant relationship between FFM and organizational commitment dimensions. Furthermore, the results of stepwise regression analyses showed that conscientiousness and openness to experience are positively associated with affective commitment. Openness to experience is negatively linked to continuance commitment, extroversion, and neuroticism is negatively associated with normative commitment.